Elite junior throwers unlikely to remain at the top level in the senior category - Boccia, G.; Cardinale, M.; Brustio, P. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study investigated (1) the transition rate of elite world-class throwers, (2) the age of peak performance in either elite junior and/or elite senior athletes, and (3) if relative age effect (RAE) influences the chance of being considered elite in junior and/or senior category.